A Cross Correlation based Back-Projection Imaging Method for Through-Wall Imaging. (August 2020) - Cai, Jiliang; Peng, Peng; Zeng, Huiyong; Wang, Shiqiang
Abstract: A back-projection (BP) algorithm based on cross-correlation (CBP), which is both fast and good at suppressing artifacts, is adopted here for through wall imaging (TWI). Firstly, by "moving" the wall to the image point, the three layer TWI modal is equivalent to the two layer TWI modal. By doing so, only half of the reflection points are needed to be calculated; secondly, to further reduce the calculation time, on the one hand, the symmetric-invariant property as well as the shift-invariant property of the ray propagation is used to calculate the look-up table, on the other hand, the delay-multiply-sum equation in CBP is rewrite into a new form with less addition and multiply computation. Simulation results show the superiority of the proposed CBP algorithm both in operation speed and artifacts suppression.